Tanggungjawab Hukum Perhimpunan Pemilik dan Penghuni Satuan Rumah Susun dalam Pengelolaan Tanah, Bagian dan Benda Bersama terhadap Pemegang Hak Milik Satuan Rumah Susun - Situmorang, Hotjen Edison; Gaol, Selamat Lumban; Sudarto, Sudarto (FOCUS, 2025)
Management of apartments and their environment is carried out by an association of residents that is formed and granted authority and responsibility in management. This study examines the form of legal responsibility of the association of owners and occupants of apartment units in managing land, parts, and common objects toward holders of apartment unit ownership rights, and how disputes related to this responsibility are resolved. The research uses a normative juridical method. Findings show that under Article 75 paragraph (3) of Law 20/2011, PPPSRS is obliged to manage the interests of owners and occupants concerning common objects, common parts, common land, and occupancy. The main purpose of establishing PPPSRS is to take necessary legal actions for the benefit of owners and occupants, maintain the environment and facilities, manage common property, and settle disputes related to these responsibilities. Disputes in apartment management require resolution efforts, and Law 20/2011 regulates this through Article 105, which includes: (a) deliberation to reach consensus, (b) settlement outside the court, and (c) court settlement. The study suggests improvements through new regulations on the association of owners and occupants of apartment units, integrated into laws, government regulations, and banking regulations, to ensure fairness for all parties. It is recommended that the government issue clear, comprehensive legal frameworks to strengthen PPPSRS’s role and accountability, providing certainty and protection to both owners and occupants in managing apartment environments.